Wonders of world architecture - 4 0 16; 1943- Parkyn, Neil; 5 (London : Thames & Hudson, 2009)
An illustrated overview of world architecture in which architects, engineers, and architectural historians discuss churches, mosques, palaces, public and state buildings, towers, skyscrapers, bridges, tunnels, dams, colossal statues, and more.
With 352 illustrations, 267 in color.;Originally published: as The seventy architectural wonders of our world. 2002.
Includes bibliographical references (p. 292-297) and index.
Adult;Adult.
Keywords: 2 -- 0; 6; History.;History.;History.;History. -- Architecture;Civil engineering;Buildings;Architektur.;Architecture;Civil engineering;Buildings -- Case studies.;Case studies; 20; 2